2015
DOI: 10.1021/acs.biomac.5b00930
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ε-caprolactone)-block-polysarcosine by Ring-Opening Polymerization of Sarcosine N-Thiocarboxyanhydride: Synthesis and Thermoresponsive Self-Assembly

Abstract: Biocompatible amphiphilic block copolymers composed of polysarcosine (PSar) and poly(ε-caprolactone) (PCL) were synthesized using ring-opening polymerization of sarcosine N-thiocarboxyanhydride initiated by oxyamine-ended PCL and characterized by NMR, SEC, and DSC. Self-assembling of two triblock copolymers PSar8-b-PCL28-b-PSar8 (CS7) and PSar16-b-PCL40-b-PSar16 (CS10) in dilute solution was studied in detail toward polymersome formation using thin-film hydration and nanoprecipitation techniques. A few giant v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 80 publications
0
42
0
Order By: Relevance
“…10 However, PEG is known to be a non-bio-based and non-biodegradable polymer with limited functionality, while studies have also shown oxidative activity of PEG in physiological cellular environments, immune response of patients and accelerated blood clearance phenomena caused by anti-PEG antibodies. [11][12][13][14] Consequently, in recent years there is a growing demand for finding alternatives to overcome these limitations of PEG. 15 A broad variety of hydrophilic polymers including poly(glycerols), 16 poly(oxazolines), 17 poly(peptides) 18 and poly(peptoids) 19 with comparable physicochemical properties to PEG have been currently explored and proposed as promising alternatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 However, PEG is known to be a non-bio-based and non-biodegradable polymer with limited functionality, while studies have also shown oxidative activity of PEG in physiological cellular environments, immune response of patients and accelerated blood clearance phenomena caused by anti-PEG antibodies. [11][12][13][14] Consequently, in recent years there is a growing demand for finding alternatives to overcome these limitations of PEG. 15 A broad variety of hydrophilic polymers including poly(glycerols), 16 poly(oxazolines), 17 poly(peptides) 18 and poly(peptoids) 19 with comparable physicochemical properties to PEG have been currently explored and proposed as promising alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…23 Over the last years, studies on the synthesis and self-assembly behavior of PSar-based block copolymers for the development of nanostructures of biotechnological interest have been presented, although they involve the use of conventional self-assembly procedures in dilute aqueous solutions. 13,23,[27][28][29][30][31][32] Recently, polymerization-induced self-assembly (PISA) has been established as an efficient methodology for facile one-pot fabrication of polymeric nano-objects with predictable morphologies at high solids concentrations (10-50% w/w). [33][34][35][36] Existing limitations of traditional self-assembly strategies (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…GUVs, which under consideration here were polymer based, can be achieved with several methods, including electroformation in sucrose or buffer solutions, swelling in solution, emulsion centrifugation, drying–rehydration, microfluidics, and thin‐film hydration based on using conventional structure amphiphilic block molecules . For example, Discher et al have previously found that the linear amphiphilic diblock copolymers, polyethyleneoxide–polyethylethylene (EO 40 –EE 37 ), can be used to prepare GUVs by electroformation in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…When dissolved in appropriate solvents, amphiphilic block copolymers show characteristic behavior and form micelles of spherical, vesicular, worm‐like and tubular structures through self‐assembly . Existing research has mainly focused on using water, instead of organic solvents, to initiate the self‐assembly of amphiphilic block copolymers . Compared with diblock copolymers, triblock copolymers possess additional morphological features and can serve as templates for the synthesis of nanoporous materials through selective removal of etchable components.…”
Section: Introductionmentioning
confidence: 99%